CFD-DEM modeling of turbidity current propagation in channels with two different topographic configurations - Lu, Yang (2023)
Submarine turbidity currents are a special type of sediment gravity flow responsible for turbidite deposits, attracting great interests from scientists and engineers in marine and petroleum geology. This paper presents a fully coupled computational fluid dynamics (CFD) and discrete element method (DEM) model to quantitatively analyze the turbidity current propagation in channels with two different topographic configurations. An appropriate drag force model is first incorporated in the CFD-DEM scheme, and two benchmark cases, including a single-particle sedimentation case and an immersed granular collapse case, are conducted to verify the accuracy of the developed CFD-DEM model. The model is then employed to investigate the fluid and particle dynamics of turbidity currents flowing over a flat bed (FB), and three obstacle-placed beds with different heights (OPB, OPB_1 and OPB_2). The CFD-DEM results indicate that the front position of turbidity current in the FB case is well consistent with the classic lock-exchange experiment. Results also show that the presence of the obstacle can clearly diminish the inter-particle collisions and the particle kinetic energy, weaken the particle-fluid interactions, and further make more sediment particles settle in front of the obstacle. Increase of obstacle height can result in diverse flow morphology of particles and fluids, and intensify the influences of obstacle on particle dynamics of turbidity currents. We show that our models enable reproducing the typical process of turbidity current propagation, and further can provide more valuable insights in understanding the turbidite-related geological phenomena from the point of view of particulate flow.